Neglect-like symptoms and their relationships with other clinical features in people with hand osteoarthritis: An exploratory study. (December 2022) - Magni, N.; Collier, J.; Rice, D.; McNair, P.
Abstract: Background: Symptomatic hand osteoarthritis (OA) is a debilitating condition. Body schema impairments such as neglect-like symptoms have been previously reported in people with symptomatic hand OA, however, little is known about their clinical importance, or relationships with other clinical features. Objectives: The aim of this cross-sectional study was to assess the prevalence of neglect-like symptoms in painful hand OA and their association with measures of depression, pain catastrophising, sleep quality, function, pain interference and pain duration whilst controlling for important covariates. Design: Secondary analysis of cross-sectional study. Methods: Logistic regression with age, sex, and worst pain intensity as covariates were utilised to assess differences between participants with and without neglect-like symptoms. Results: A total of 121 participants were recruited. Sixty-one percent of participants presented with neglect-like symptoms. Participants with longer pain duration had greater odds of presenting with neglect-like symptoms (OR: 1.10 95%CI: 1.01 to 1.19; p = 0.012). No difference was observed for depression, pain catastrophising, sleep quality, function, or pain interference. Conclusions: A large proportion of participants with symptomatic hand OA reported neglect-like symptoms, the presence of which was associated with longer pain duration. Highlights: Neglect-like symptoms are present in 60% of people with symptomatic hand OA. Neglect-like symptoms are associated with longer pain duration. Interventions to modify body perceptual disturbances may help people with hand OA.